METODE CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN BAHASA ARAB - Ilham Muchtar (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2017)
AbstractThe concept of Contextual Teaching and Learning (CTL)  emphasizes on the  student activity, both physically and mentally. Contextual Teaching and Learning believe that learning is not just about  memorizing, , considering or remembering facts, demonstrating repetitious exercise but it is  a process of experience in real life  with the nature ( environment). Contextual Teaching and Learning in  Arabic teaching and learning process is believed to improve student’s  achievement in learning Arabic because they will get so much eager to learn or they will have the confidence to know something that has not been known so the pupils are not depressed  in teaching and learning process.Keywords: Activities, Contextual Teaching and Learning (CTL), Achievement AbstrakKonsep pembelajaran Contextual Teaching and Learning (CTL) menekankan pada aktivitas siswa secara penuh, baik fisik maupun mental. Contextual Teaching and Learning memandang bahwa belajar bukanlah kegiatan menghafal, mengingat fakta-fakta, mendemonstrasikan latihan secara berulang-ulang semata akan tetapi proses berpengalaman dalam kehidupan nyata di alam terbuka. Contextual Teaching and Learning dalam pembelajaran bahasa Arab diyakini dapat meningkatkan prestasi belajar siswa dalam belajar bahasa Arab karena peserta didik semakin bersemangat belajar ataupun mempunyai kepercayaan diri untuk mengetahui sesuatu yang belum diketahui sehingga membuat peserta didik tidak tertekan dalam proses belajar mengajar.Kata Kunci: Aktifitas, Contextual Teaching and Learning (CTL), Prestasi.